Organizacja i funkcjonowanie podmiotów gospodarczych cukrownictwa polskiego - Kapusta, Franciszek (Organization and Functioning of Enterprises of Polish Sugar Industry, 2005)
Sugar industry is functioning within a regulated market and demands specific sort of organization and management. Organization of Polish sugar industry has changed and at the beginning of the 21st century it took the form of companies and holding companies functioning as an integrated net.Companies and capital groups, having limited scope of production and prices (of finished products and basic raw materials) concentrate their efforts on increasing the gain through perfection of processing organization and through cost cuts. Although each company and capital group develops a unique strategy, there are many similarities and différencies pertain mainly the pace of implementation of selected elements of the strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 316-323